2005
DOI: 10.1038/sj.jcbfm.9600060
|View full text |Cite
|
Sign up to set email alerts
|

Long Duration Stimuli and Nonlinearities in the Neural–Haemodynamic Coupling

Abstract: Recent studies have shown that the haemodynamic responses to brief (o2 secs) stimuli can be well characterised as a linear convolution of neural activity with a suitable haemodynamic impulse response. In this paper, we show that the linear convolution model cannot predict measurements of blood flow responses to stimuli of longer duration (42 secs), regardless of the impulse response function chosen. Modifying the linear convolution scheme to a nonlinear convolution scheme was found to provide a good prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 33 publications
6
59
2
Order By: Relevance
“…Disagreement between rat and human studies-Human fMRI studies have found nonlinearity of the hemodynamic response to short stimuli durations (<2 s) (Birn et al, 2001;Liu and Gao, 2000;Nangini et al, 2006), while animal studies have found non-linearity of the hemodynamic response for long stimuli duration (>8 s) (Ances et al, 2000;Martindale et al, 2005;Ureshi et al, 2004). Martindale et al (Martindale et al, 2005) suggest that this discrepancy is attributable to different analysis methods.…”
Section: Area Under the Curve Vs Peak Amplitude Of Sep Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disagreement between rat and human studies-Human fMRI studies have found nonlinearity of the hemodynamic response to short stimuli durations (<2 s) (Birn et al, 2001;Liu and Gao, 2000;Nangini et al, 2006), while animal studies have found non-linearity of the hemodynamic response for long stimuli duration (>8 s) (Ances et al, 2000;Martindale et al, 2005;Ureshi et al, 2004). Martindale et al (Martindale et al, 2005) suggest that this discrepancy is attributable to different analysis methods.…”
Section: Area Under the Curve Vs Peak Amplitude Of Sep Componentsmentioning
confidence: 99%
“…Martindale et al (Martindale et al, 2005) suggest that this discrepancy is attributable to different analysis methods. Essentially, the smaller SNR and lower temporal resolution of BOLD fMRI makes problematic the measure at short durations.…”
Section: Area Under the Curve Vs Peak Amplitude Of Sep Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have found that brief stimuli (<4 s) elicit hemodynamic signals that cannot be well-characterized using the simplest version of the convolution model based on using the stimulus envelope as an input waveform [e.g., Boynton et al, 1996;Pfeuffer et al, 2003;Vazquez and Noll, 1998]. However, animal studies that incorporate electrophysiological measurements of neural activity have found that responses to brief stimuli (<4 s) do not deviate from linearity [e.g., Ances et al, 2000;Martindale et al, 2003Martindale et al, , 2005. Several authors have suggested that nonlinearities in the signaling process between stimulus input to neural response may account for this discrepancy, such as adaptation of the neural signal [Boynton et al, 1996;Miller et al, 2001;Nangini et al, 2005;Pfeuffer et al, 2003;Soltysik et al, 2004].…”
Section: Introductionmentioning
confidence: 98%
“…Because BOLD fMRI signal linearity studies in humans have not been conducted with a complementary neural measurement, it is unknown whether the failure of the convolution model is based on poor representation of the neural activity input to the convolution model [Martindale et al, 2005], or deviation from the convolution model itself. The natural next step is to investigate whether replacing the stimulus boxcar waveform with an appropriate waveform derived directly from MEG measurements can provide better characterization of BOLD signal behavior under the convolution model for different duration stimuli.…”
Section: Introductionmentioning
confidence: 99%